Pengaruh Profitabilitas dan Leverage Pada Earning Response Coefficient Dengan Ukuran Perusahaan Sebagai Variabel Pemoderasi - Sutrisna Dewi, Nyoman; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 26 No 3 (2019)DO - 10.24843/EJA.2019.v26.i03.p14, 2019)
This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. The sample obtained was 58 companies with 174 observations. Determination of the sample using non probability sampling method with purposive sampling technique. The data analysis technique used is the Moderated Regression Analysis test. Based on the results of this study it was found that profitability and leverage had a negative effect on the ERC. The higher the company makes a profit and the higher the leverage level it has, the lower the ERC value of the company. It was found that Company size can weaken the influence of profitability on the ERC and company size can  strengthened the influence of leverage on the ERC. Keywords:  Profitability, leverage, company size, earnings response coefficient